PENGARUH BEBAN OPERASIONAL PENDAPATAN OPERASIONAL (BOPO), NON PERFORMING FINANCING, DAN UKURAN PERUSAHAAN TERHADAP TINGKAT EFISIENSI PERBANKAN SYARIAH DI INDONESIA - Rizka Fauzi; Rulfah M Daud (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2020)
This research  aims to investigate  the influence  of BOPO,  Non Performing  Financing,  and Firm  Size on Efficiency Level of Islamic Banking in Indonesia. The efficiency score is obtained using Data Envelopment Analysis (DEA) Method. The type of data employed is secondary data from financial statements of each banks between 2014 and 2018. The results of this research indicate that (1) Operating Expenses against Operating Income, Non Performing Financing,  and  Firm  Size  simultaneously  affect  the  efficiency  level,  (2)  Operating  Expenses  against  Operating Income does not affect the efficiency level, (3) Non Performing Financing does not affect the efficiency level, and (4) Firm Size affects the efficiency level of islamic banking in Indonesia